BANCO MÓVIL PARA VERIFICACIÓN DE CAUDALÍMETROS EN SITIO COMO ESTRATEGIA DE APOYO AL SECTOR MANTENIMIENTO DE SISTEMAS DE INSTRUMENTACIÓN INDUSTRIAL - HIGUERA , CRISTHIAM LEONARDO
To maintain the quality of the production processes, it is not enough to acquire the technology; to ensure its correct operation it is also necessary to maintain the equipment; one of these tasks is verification and/or calibration. According to information consulted at the National Accreditation Body of Colombia (ONAC), so far in the department of Santander there is only one laboratory accredited for the calibration of Coriolis CDT flow meters for GAS, and no laboratory for electromagnetic or ultrasonic transmitters for liquid measurement. The objective of this project is to continue strengthening knowledge on flow measurement of liquid fluids through the development of a metrological infrastructure for the calibration of mass, gravimetric and volumetric flow meters at the Industrial and Technological Development Center CIDT Barrancabermeja.